The Effect of cocoa pod husk (Theobroma cacao L.) extract on alveolar socket post tooth extraction - Rahayu, Yani Corvianindya; Yuwono, Budi; Syafriadi, Mei; Amin, Muhammad Nurul; Kumala, Efa Ayu Ratnaning (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2025)
Background: Cocoa pod husk (CPH) of Theobroma cacao L. contains tannins, alkaloids, saponins, and flavonoids triterpenoids that have antibacterial, anti-inflammatory, and antioxidant activities that can accelerate wound healing and alveolar bone regeneration. Purpose: This study aimed to analyze the effect of CPH extract gel on the number of fibroblasts, osteoblasts, and osteoclasts in Wistar rats’ sockets after tooth extraction. Methods: The samples used were 36 male Wistar rats divided into three groups: the negative control group (placebo gel), the positive control group (Alveogyl; Septodont, UK), and the treatment group (100 mg/ml CPH extract gel), which in each application was given for three, seven, and fourteen days on the mandibular first molar post-extraction socket. The samples were sacrificed and tissue was processed on days 4, 8, and 15. The amount of fibroblasts, osteoblasts, and osteoclasts was identified and determined by the Image J software. Results: The Mann-Whitney U analysis showed significant differences (p<0.05) between groups. Fibroblasts and osteoblasts in the treatment group were significantly higher than the control groups. Osteoclasts in the treatment group were significantly lower than the control group. Conclusion: Ethanol extract gel of CPH significantly increased fibroblasts on days 3 and 5 and osteoblasts on days 7 and 14 and decreased osteoclasts on day 14 in post-extraction socket of Wistar rats.